2014
DOI: 10.1208/s12249-014-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Caprylate-Conjugated Cisplatin for the Development of Novel Liposomal Formulation

Abstract: Abstract. Cisplatin, first (platinum) compound to be evolved as an anticancer agent, has found its important place in cancer chemotherapy. However, the dose-dependent toxicities of cisplatin, namely nephrotoxicity, ototoxicity, peripheral neuropathy, and gastrointestinal toxicity hinder its widespread use. Liposomes can reduce the toxicity of cisplatin and provide a better therapeutic action, but the low lipid solubility of cisplatin hinders its high entrapment in such lipid carrier. In the present investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In previous reports, various drug delivery systems have been developed for enhancing the antitumour effect of the active ingredients, such as micelles, liposomes and nanoparticles . Among these delivery systems, liposome is considered to be a stronger prospective alternatives as several of these formulations have been under clinical assessment for anticancer . However, the traditional liposomes came with some serious problems, such as instability, insufficient drug loading, fast drug release and short blood circulation .…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, various drug delivery systems have been developed for enhancing the antitumour effect of the active ingredients, such as micelles, liposomes and nanoparticles . Among these delivery systems, liposome is considered to be a stronger prospective alternatives as several of these formulations have been under clinical assessment for anticancer . However, the traditional liposomes came with some serious problems, such as instability, insufficient drug loading, fast drug release and short blood circulation .…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery carriers are also suitable for use with cisplatin, including NPs, liposomes, micelles (Baba et al, 2012), and nanocapsules (Boulikas, 2009;Vhora et al, 2014). These can selectively and effectively accumulate in solid tumors, enhancing anticancer potential and reducing toxicity.…”
Section: Othersmentioning
confidence: 99%
“…Vhora et al reported that the sterol cisplatin-based liposome demonstrated the greater half-life as a match free drug. The X-ray fluorescence spectroscopy technique was used to determine the platinum content in the formulation [85]. Another research group reported that the liposomes formulation was designed to overcome the problem regarding poor solubility of cisplatin, improvement of the therapeutic index and safety profile [86].…”
Section: Liposomesmentioning
confidence: 99%